Assessment of glycaemic control in patients with type 2 diabetes: a clinic-based study in a slum of Kolkata - Pan, Tania; Dasgupta, Aparajita; Suman, Sweta; Paul, Bobby; Banerjee, Rajarshi; Burman, Jayeeta (International Journal Of Community Medicine And Public Health, 2018)
Background: Although diabetes is a chronic condition, it can be controlled and managed to prevent complications. Long-standing diabetes with poor glycaemic control leads to many complications. This study aims to assess the glycaemic control status and its associated factors among type 2 diabetes patients attending Urban Health Centre in a slum of Kolkata, West Bengal. Methods: A clinic-based cross-sectional study was conducted among 184 diabetic patients attending clinic at Urban Health Centre, Chetla from October-December 2017. Each respondent was interviewed using a structured schedule to collect data on sociodemographic characteristics, physical activity, disease profile and self-care activities. Height and weight were measured. Individuals with PPBS ≥160 mg/dl were said to have poor glycaemic control. Data entry and analysis was done using SPSS version 16.0. Results: Out of 184 participants, 37.5% had poor glycaemic control. Mean (±SD) age of the participants was 51.64 (9.64) years. Median duration of diabetes was 4 years. 104 (56.5%) had overweight/ obesity. Only 26.6% had satisfactory dietary practice. Test results revealed ≥4 years duration of diabetes, overweight/ obesity, smoking, unsatisfactory diet and non-adherence to medications as significant predictors of poor glycaemic control, explaining 31.6% of the variance of glycaemic control with non-significant Hosmer–Lemeshow statistics. Conclusions: The study has identified factors associated with poor glycaemic control among the study participants. Emphasis on promoting a healthy lifestyle which includes a healthful eating plan, cessation of smoking, maintaining optimum body weight and strictly adhering of prescribed medications would go a long way in maintaining good glycaemic control.